Identifying the Origin of Galactic Cosmic Rays with the SuperTIGER Instrument - Murphy, Ryan Patrick (Washington University Open Scholarship, 2015)
The SuperTIGER (Trans-Iron Galactic Element Recorder) experiment was launched on a long-duration balloon flight from Williams Field, Antarctica, on December 8, 2012. The instrument measured the relative elemental abundances of galactic cosmic rays (GCR) in the charge (Z) range Z>10 with excellent charge resolution, displaying well resolved individual element peaks for 10 ≤ Z ≤ 40. During its record-breaking 55-day flight, SuperTIGER collected ~4.15 x10^6 Iron nuclei, ~ 7.5 times as many as detected by its predecessor, TIGER, with charge resolution at iron of < 0.18 cu. SuperTIGER measures charge (Z) and energy (E) using a combination of three scintillator and two Cherenkov detectors, and employs a scintillating fiber hodoscope for event trajectory determination. The SuperTIGER data have been analyzed to correct for instrument effects and remove events that underwent nuclear interactions within the instrument. The data include more than 600 events in the charge range 30 < Z ≤ 40. SuperTIGER is the first experiment to resolve elemental abundances in this charge range with single-element resolution and high statistics. The relative abundances of the galactic cosmic ray source have been derived using atmospheric and interstellar propagations of the measured relative elemental abundances. The SuperTIGER measured abundances are generally consistent with previous experimental results from TIGER and ACE-CRIS, with improved statistical precision. The SuperTIGER results confirm the earlier results from TIGER, supporting a model of cosmic-ray origin in OB associations, with preferential acceleration of refractory elements over volatile elements ordered by atomic mass (A).